Understanding Human Organ Trading: Ethical Perspective and Indonesia's Legal Framework - Dedy Indriyanto; Liliana Tedjosaputro; Totok Tumangkar; Afif Noor (Qubahan Academic Journal)
Human organ trading has become an increasingly complex and controversial issue in the era of globalization. This article aims to explore an in-depth understanding of human organ trading through ethical perspectives and in the context of Indonesia's legal framework. By combining ethical and legal studies, this article summarizes ethical views on human organ trading and analyzes the relevance of Indonesia's legal framework in addressing the challenges of such trading. In the process, it considers the implications of moral and religious values for human organ trading. Through an interdisciplinary approach, the article seeks to compile the contributions of ethics and law in forming a comprehensive view of this complex issue. It is hoped that a deeper understanding of ethical perspectives and legal frameworks will provide richer insights into human organ trading and encourage constructive debate to address the issue.